DIGITAL TRANSFORMATION IN EDUCATION: FACING THE TECHNOLOGY AGE - Novianty Djafri; Ignatius Septo Pramesworo; Khasanah; Mardi Widodo; Muhammad Nurhisyam Ali Setiawan (Adisam Publisher, 2024)
Digital transformation in education is one of the most significant and pressing topics in today's technological age. The research aims to dig out how educational institutions and related stakeholders respond to the challenges and take advantage of the opportunities brought by the digital age. Using a qualitative and quantitative approach, the study explores a variety of strategies applied by schools, universities, and other educational institutions in integrating digital technology into curricula, teaching methods, and learning processes. The results of the study show that digital transformation has brought significant changes in the way of teaching and learning, including improved accessibility of learning materials, personalization of the learning process, and the use of innovative digital tools. However, the research also identifies a number of challenges, such as digital gaps, the need for teacher training, and issues related to privacy and data security. In the face of the technology age, the study emphasizes the importance of collaboration between governments, educational institutions, the technology industry, and communities to ensure that digital transformation in education is implemented effectively and inclusive. The resulting advice aims to assist stakeholders in formulating policies, strategies, and practices that can improve the quality of education through the optimal use of digital technology.